Simulation of piezoelectric energy device in the pavement of urban crossroad - Pinto, Paulo César (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Energy Harvesting is a concept that aims to transform the weight of the vehicle traveling on a track into electrical energy, converting mechanical pressure into electricity, it is the principle of piezoelectric technology currently being tested on highways and urban roads around the world. This type of energy varies depending on the load quantity of the vehicle and the number of times it passes, consequently, this form of energy is discontinuous, being the best use when used on roads with a high flow of vehicles. In this context, a study based on the implementation of piezoelectric devices at an urban intersection with traffic lights in three Brazilian cities with different ports is presented: Marau, Erechim and Passo Fundo. Piezoelectric energy still shows the initial phase of technological and experimental development, but it shows the potential for use in the urban environment, mainly due to the concentration of light vehicles, speeds and as a complementary alternative existing in the existing electrical network.